Analysis of the fertilizing potential of sewage sludge and its impact onagriculture and the environment - Nadjet Mesbah; Meriem Amina Rezki Bekki; Linda Aouad; Omar Rouane Hacene; Gaël Durand; Abdelkader Bekki (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: The management of sewage sludge represents a major environmental challenge on a global scale, as poor management can lead to significant risks for public health and the environment. This study aims to assess the fertilizing potential of sludge and its impact on agriculture and the environment, offering a sustainable solution for recovering this waste while improving soil fertility.